[SnBi3]5− —A Carbonate Analogue Comprising Exclusively Metal Atoms. Issue 47 (24th October 2017) - Mayer, Kerstin; Dums, Jasmin V.; Klein, Wilhelm; Fässler, Thomas F.
Abstract: The new [SnBi3 ] 5− polyanion is obtained by the reaction of K3 Bi2 with K4 Sn9 or K12 Sn17 in liquid ammonia. The anion is iso(valence)electronic with and structurally analogous to the carbonate ion. Despite the high negative charge of the anion, the Sn−Bi bond lengths range between single and double bonds. Quantum‐chemical calculations at a DFT‐PBE0/def2‐TZVPP/COSMO level of theory reveal that the partial double bond character between the heavy main‐group atoms Bi and Sn originates from a delocalized π‐electronic system. The structure of the anion is determined by single‐crystal X‐ray diffraction analyses of the compounds K5 [SnBi3 ] 9 NH3 (1 ) and K9 [K(18‐crown‐6)][SnBi3 ]2 ⋅15 NH3 (2 ). The [SnBi3 ] 5− unit is the first example of a carbonate‐like anion obtained from solution, and it consists exclusively of metal atoms and completes the series of metal analogues of CO and CO2 . Abstract : Carbonate build up by metals : Whereas alkali metal carbonates are mostly insoluble in liquid ammonia, a carbonate analogue is formed by Bi and Sn by reaction of deeply colored solutions of polyanionc bismuthides and stannides in liquid ammonia and can be isolated as the potassium salt K5 SnBi3 ⋅9 NH3 . In contrast to carbonate, the highly charged [BiSn3 ] 5− ion decomposes readily in the presence of traces of water.